2016
DOI: 10.1088/0957-0233/27/8/085701
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous recording of the action potential and its whole-cell associated ion current on NG108-15 cells cultured over a MWCNT electrode

Abstract: It is well known that, in excitable cells, the dynamics of the ion currents (I i) is extremely important to determine both the magnitude and time course of an action potential (A p). To observe these two processes simultaneously, we cultured NG108-15 cells over a multi-walled carbon nanotubes electrode (MWCNTe) surface and arranged a two independent Patch Clamp system configuration (Bi-Patch Clamp). The first system was used in the voltage or current clamp mode, using a glass micropipette as an electrode. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
2
4
0
2
Order By: Relevance
“…The current traces of devices D1–D3 demonstrated regular firing frequencies (Figure d, left panels) and signal shapes (Figure d, right panels). The electrophysiological signal observed is similar to that reported in other studies of the whole–cell ion current recorded by the multiwalled CNT electrode . Meanwhile, the stable and regular current traces further suggested that robust interfaces were formed between CNT–silk and cardiomycytes.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The current traces of devices D1–D3 demonstrated regular firing frequencies (Figure d, left panels) and signal shapes (Figure d, right panels). The electrophysiological signal observed is similar to that reported in other studies of the whole–cell ion current recorded by the multiwalled CNT electrode . Meanwhile, the stable and regular current traces further suggested that robust interfaces were formed between CNT–silk and cardiomycytes.…”
supporting
confidence: 87%
“…The electrophysiological signal observed is similar to that reported in other studies of the whole−cell ion current recorded by the multiwalled CNT electrode. 22 Meanwhile, the stable and regular current traces further suggested that robust interfaces were formed between CNT−silk and cardiomycytes. These results show that the CNT−silk-based devices are capable of recording the spontaneous electrophysiological activity of different cardiomy- cytes simultaneously, and the electrophysiological changes that might occur during the primary culture can be identified and characterized.…”
mentioning
confidence: 99%
“…The latter problem had been partially solved by other approaches ( Dietrich et al., 2002 ; Banyasz et al., 2011 ; Barra, 1996 ; Bean, 2007 ; Berecki et al., 2005 ; Doerr et al., 1990 ; Economo et al., 2010 ; Nowotny et al., 2006 ; Molnar and Hickman, 2007 ; Wilders, 2006 ; Hille, 1994 ; Levitan, 1994 ). Very recently, it was fully solved by using carbon nanotubes (maintained at virtual ground) as a substrate for cell culturing ( Morales-Reyes et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…with good signal to noise ratio) of the action potentials and the underlying ionic currents ( Dietrich et al., 2002 ; Banyasz et al., 2011 ; Barra, 1996 ; Bean, 2007 ; Berecki et al., 2005 ; Doerr et al., 1990 ; Economo et al., 2010 ; Nowotny et al., 2006 ; Molnar and Hickman, 2007 ; Wilders, 2006 ). Recently, this limitation was overcome by using carbon nanotubes as a substrate for cell culturing ( Morales-Reyes et al., 2016 ). In this work, we propose that gold substrates can be used instead of carbon nanotubes to perform simultaneous measurements of electrical activity and the underlying membrane currents.…”
Section: Introductionmentioning
confidence: 99%
“…The culture of neurons on peptide coated gold surfaces [265,266] and multielectrode microarrays has facilitated the measurement of generated membrane action potentials and whole-cell ion currents. [267][268][269] Culture of NG108-15 cells on gold surfaces has improved the analysis of intracellular ioncurrents and membrane potentials in cultured neurons. [98] AFM and SEM has also been applied to the characterization of these cells [270][271][272] and to determine the roles of regulatory ion channels, [273,274] and how these are modulated by G-coupled receptors [275] and the sensory input of fillopodia in neuronal cultures.…”
Section: Future Areas Of Investigation Into the Function And Therapeu...mentioning
confidence: 99%